Aquinas's views on mind and soul: echoes of Platonism - Quinn, Patrick (Verbum – Analecta Neolatina, 2004)
St. Thomas's views on the human soul and mind are shaped by Platonic as well as Aristotelian influences. His account of the human soul as the substantial principle and form of human life quickly becomes translated into a definition of the soul as an intelligent substance that exists on the boundary line of bodily and non-bodily substances as though it were on the horizon of time and eternity, according to Summa contra Gentiles, Book 11, Chapter 81. The human being as a whole is also described in this way in Summa Theologica 1.77.2. This “boundary” image of the human being allows St. Thomas in Summa Theologica 1.89.1 to account for how knowledge can occur in the absence of the body after death. It also enables Aquinas to explain in other texts how religious ecstasy can occur in life before death in that the sensory powers are supernaturally suspended to free the mind to see God. Thus non-bodily based knowledge before or after death with all the important implications involved are philosophically accounted for, at least up to a point, by Platonism. This is not to deny Aquinas's Aristotelianism but simply to note the existential importance of Platonic insights in his thinking also, especially when St. Thomas attempts to philosophically present his views on how knowledge occurs in human beings in the absence of the senses.